Four new species of Guimaraesiella (Phthiraptera: Ischnocera: Brueelia-complex) from China - Gustafsson, Daniel R.; Tian, Chunpo; Ren, Mengjiao; Liu, Zhixiao; Yu, Xiaoping; Zou, Fasheng (Zootaxa, 2021)
Four new species of Guimaraesiella Eichler, 1949 are described and illustrated based on specimens collected in South China. They are: Guimaraesiella (Cicchinella) citreisoma new species ex Leiothrix lutea kwangtungensis Whistler, 1943 (Leiothrichidae); Guimaraesiella (Cicchinella) corrugata new species ex Alcippe hueti hueti David, 1874 (Leiothrichidae); Guimaraesiella (Cicchinella) petilorica new species ex Alcippe nipalensis nipalensis (Hodgson, 1837) (Leiothrichidae); and Guimaraesiella (Cicchinella) yuhinae new species from Yuhina flavicollis rouxi (Oustalet, 1896) (Zosteropidae); this is the first species of the Brueelia-complex recorded from a member of the Zosteropidae.